Profissionalização docente e legislação educacional: Uberabinha (1892-1930) - Vieira, Flávio César Freitas (2004)
This dissertation proposes to present the transformations in the teacher s professionalization based on educational legislation in Uberabinha, between the years 1892 and 1930, as one of the aspects of insertion in the uberabinhense society involved in a modern atmosphere. Those transformations will be studied founded on discussions originating in Modern State liberal principles, on Constitutional Law and the Republican Constitutions, Federal and State, on Municipal Legislation and on the progressive registers stablished for legislation on educational area, which versify, principally, about rights and duties of involved subjects in the dynamic of teacher s professionalization, besides this professional profile changes through the focused period in the First Republic. The consulted sources, to get the aims of this research, are non-official documents as written and periodical press registers of the period, besides official papers as Proceedings and Town hall of Uberabinha Reports and the Municipal Inspector documents. The official documentation points to subjects and social and institutional acts legitimating an insertion process in the modernity, showing the teacher s professionalization quest as a participant element in the modernization process of a society in transition, it means, form antiquated, as all imperial things, to the modern, the Republic; from amateur to professional; for volunteer to professional teacher, who was considered a fundamental element to the Republic maintenance. In this transition, the teacher s professionalization in Uberabinha can be understood through three moments: the construction (1892-1899); the consolidation (1899-1923) and the modernization (1923-1930), all these aspects involved on the teaching staffs constitution, which passed from the first to the last moment, from the volunteer teacher to the normal teacher, valorizing the urban context in detriment of the rural.